2011
DOI: 10.1021/nl201850k
|View full text |Cite
|
Sign up to set email alerts
|

High Quantum Efficiency of Band-Edge Emission from ZnO Nanowires

Abstract: External quantum efficiency (EQE) of photoluminescence as high as 20% from isolated ZnO nanowires were measured at room temperature. The EQE was found to be highly dependent on photoexcitation density, which underscores the importance of uniform optical excitation during the EQE measurement. An integrating sphere coupled to a microscopic imaging system was used in this work, which enabled the EQE measurement on isolated ZnO nanowires. The EQE values obtained here are significantly higher than those reported fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
65
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 18 publications
5
65
0
Order By: Relevance
“…Therefore characterization depends on the nature and structure of the imperfection and the electronic states of the solid. [59][60][61][62][63]67,68 In particular, all the defects discussed above play a key role in streamlining the physical and chemical properties of semiconductor materials directly associated with the structural and electronic order-disorder effects which can exist in ZnO nanocrystals with different charged states or in a neutral state typically represented by V [60][61][62][63]72,73 which are generated in the rapid crystallization of such materials during the MAH process, and have been reported in this study. In this case, experimental results presented in Fig.…”
Section: -66mentioning
confidence: 62%
See 2 more Smart Citations
“…Therefore characterization depends on the nature and structure of the imperfection and the electronic states of the solid. [59][60][61][62][63]67,68 In particular, all the defects discussed above play a key role in streamlining the physical and chemical properties of semiconductor materials directly associated with the structural and electronic order-disorder effects which can exist in ZnO nanocrystals with different charged states or in a neutral state typically represented by V [60][61][62][63]72,73 which are generated in the rapid crystallization of such materials during the MAH process, and have been reported in this study. In this case, experimental results presented in Fig.…”
Section: -66mentioning
confidence: 62%
“…67,68 In particular, Van Vugt et al 69 have reported a strong exciton-photon coupling in ZnO nanowires at room temperature. The phononassisted recombination determines the temperature-dependence of the PL signal intensity which decreases with an increase in temperature due to phonon-assisted transition effects in the ZnO crystal.…”
Section: -66mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that, at least for the majority of cases, room-temperature lasing in ZnO nanowires does not involve excitons. Parameters affecting the laser threshold are the nanowire dimensions [13,33], the quality of the nanowire, which is strongly dependent on the growth conditions [34], and the substrate supporting the wire [35].…”
mentioning
confidence: 99%
“…It should be noted that the use of Ag nanoparticles in packages has several advantages over semiconductor luminescent nanoparticles and luminescent particles of other metals; namely, Ag nanoparticles can have higher quantum luminescence yields than ZnO [19][20][21], and they are nontoxic in contrast to CdS and CdSe. Colloidal Au nanoparticles are stable while utilized for nanophotonic applications related to light trapping [22], but Ag nanoparticles are significantly cheaper than Au nanoparticles.…”
Section: Introductionmentioning
confidence: 99%